TEXTBOOK ANALYSIS ON COLLEGE ACADEMIC WRITING - Handoyo Puji Widodo (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
Abstract: When no specific materials are available particularly on EFL writing courses, the selection and use of a textbook are of great priority. For this reason, this article analyzes a textbook on college academic writing in an EFL context-Indonesia. In this analysis, I employed the in-depth method using the three phases of the textbook analysis, concerning the three main features of the textbook: (1) goal and organization, (2) contents-inputs, models, and exercises, and (3) the suitability of the textbook viewed from aims, beliefs about writing, the roles of the teacher, the role of the students, and the roles of the textbook as a whole. The extent to which the selected textbook reflected the recent views of the teaching and learning of writing skill was also investigated. The results show that the author echoed his clear goal and organization. The contents of the textbook regarding the inputs, models, exercises, and writing assignments reflected the features of academic writing required for college students.